Designing conditionality in the supply of European public goods - Roel Beetsma; Marco Buti (Bruegel, 2024)
The European Union will need in the coming years to invest a substantial amount of resources in European public goods (EPGs), including for the digital and climate transitions, and for defence and security. Funding for this could be provided in a centralised way at EU level, via either a fund or from the EU budget, but for this to be politically viable, and to create the necessary trust, national budgetary policies need to comply with the common EU fiscal rules. Setting adequate conditions for access to central financing is, however, not straightforward. The tightness of the conditionality needs to balance the desirability of a country pursuing sound fiscal policies with the need to deliver on the provision of EPGs that benefit several or all EU countries. The optimal tightness should reassure fiscally-conservative countries that EU money would not result in opportunistic behaviour that results in less discipline at national level. More fiscally fragile countries should be reassured that their fiscal retrenchment efforts will be duly rewarded.
Keywords: 330; eu governance; eu budget